A proposed methodology to assess the state of Islamic inputs in the courses offered by the Kulliyyah of Architecture & Environmental Design, International Islamic University Malaysia - Ahmad Sarkawi, Azila; Abdul Rashid, Khairuddin (2015)
Islamisation of human knowledge (IoHK) concerns every aspects of acquired knowledge including the built environment’s body of knowledge. In the era of secularization and the dualism educational system that domineering the world, IoHK becomes a critical agenda. Integration rather than coexistence between secular and Islamic form of knowledge is highly expected in educational system without compromising the sacredness of Islam. Being an Islamic University, the agenda was already in place since the establishment of IIUM in 1983. It is timely for assessing the achievement of this agenda in particular the courses offered. Subsequently, few studies have been conducted to assess the state of Islamic input in the courses offered by KAED, IIUM. Hence, the paper presents the methodology adopted in the assessment. The methods were content analysis, focus group discussion (FGD) and questionnaire survey. For content analysis, keywords like Islam, ethics, promoting good and forbidding bad appeared throughout course outlines were identified and analysed to come out with its state of Islamic input. The outcome of the content analysis was presented in the FGD comprising experts in the subject matter. FGD was a method used to get feedback from the experts consequently validated the preliminary findings. Alternatively, questionnaire survey method could also be used to assess the state of Islamic input in the courses offered. The Islamisation modes produced by Center for Islamisation (CENTRIS), IIUM were used as construct of the survey which was then contrasted with the fourteen weeks of teaching. The survey revealed the percentage of Islamic input ranging from 0-20 (poor); 21-40 (low); 41-60 (average); 61-80 (good); and 81-100 (excellent). The survey also collates modes of Islamisation took place in KAED from the lecturers’ perspective. Finally it can be said that this methodology appeared to be successfully attaining the objectives of the study that was to assess the state of Islamic input and the modes of Islamisation taking place in courses offered.